Experimental characterisation of the self-excited vibrations of spring-loaded valves. (January 2018) - El Bouzidi, Salim; Hassan, Marwan; Ziada, Samir
Abstract: Valves are omnipresent in industrial processes. As a result, they must perform reliably according to their specifications. Spring-loaded valves are particularly susceptible to vibrations, as they are inherently flexible, often operate at small openings, and therefore they are more likely to interact with the surrounding flow. The current study experimentally investigates the self-excitation mechanism of a model spring-loaded valve with an emphasis on the interaction between the system flow and sound fields, and the valve structure. Tests are performed for various values of valve stiffness and maximum allowable valve lift. In each case, the pressure drop across the valve is increased gradually until the valve becomes fully open. The valve was found to oscillate at the fully coupled resonance frequency resulting from the interaction of the valve vibration with the acoustic field of the piping system. The oscillation amplitude was found to be positively correlated to both the pipe length and spring stiffness value. Furthermore, initial spring compression was found to have only moderate effects on the range of static pressures that would cause instability. Highlights: Dynamic instability of a spring-loaded valve is investigated. The excitation mechanism is due to acoustic, structural, and hydrodynamic coupling. Limit cycle behaviour is observed for cases below the maximum valve lift. Increasing the valve spring stiffness is seen to cause more severe vibrations. Increasing the length of the piping is seen to destabilise the valve as well. The instability mechanism is analogous to that seen in compressor disk-type valves.